The Prevalence of Dysphagia in Children with Laryngomalacia Pre and Postsupraglottoplasty: A Systematic Review with Meta-Analysis - Rossoni, Eduarda Pinto; Miranda, Vanessa Souza Gigoski de; Barbosa, Lisiane De Rosa (International Archives of Otorhinolaryngology, 2024)
Introduction Laryngomalacia is the most common congenital laryngeal alteration, with spontaneous resolution in most cases. However, in the face of more severe presentations of the disease, it is necessary to perform supraglottoplasty surgery. Studies have been dedicated to researching changes in swallowing in children with laryngomalacia before and after surgical intervention.Objectives To identify the prevalence of oropharyngeal dysphagia in children with pre and postsupraglottoplasty laryngomalacia.Data Synthesis A search strategy was developed with terms and entreterms to designate a population pediatric with laryngomalacia, exposure supraglottoplasty, and outcome frequency of dysphagia, adapted to the requirements of the main databases in the health area. The analysis of the records found was performed by two independent examiners and, in the end, 6 articles were included in the study. The articles found enabled a sample of 330 children with laryngomalacia, 311 of whom underwent supraglottoplasty. Among the included studies, 5 were grouped and meta-analyzed. After supraglottoplasty surgery, a 59% reduction in the prevalence of oropharyngeal dysphagia was identified, with high heterogeneity I2 = 93%.Conclusion Despite the heterogeneity of the sample, the supraglottoplasty procedure significantly reduces the prevalence of dysphagia in children with laryngomalacia.
Keywords: infant; newborn; deglutition; deglutition disorders; laryngomalacia; aspiration